Засновок концепції "безґрунтовності" Віктора Петрова - Брюховецький, В.С. (Слово і Час, 2019)
У статті розглядається взаємодія літератури з дійсністю в різних контекстах. Термін “знедійснення
дійсності” був запропонований В. Петровим (В. Домонтовичем) наприкінці 1940-х років.
Перші рефлексії над цим явищем належать М. Євшану стосовно творчості Лесі Українки (1913).
Тогочасне українське життя не надавалося поетесі для пошуку ґрунту модерного естетичного
розвитку. Подібне можна спостерегти й у творчості М. Гоголя.
В. Петров у концепціях “знедійснення дійсності” і “безґрунтовності” наближався до
екзистенціальних ідей Л. Шестова (“Апофеоз безґрунтовності”, 1905). Багатозначність терміну
“безґрунтовність” дозволяє використовувати його в різних контекстах – від філософськи
значущого (як у Г. Сковороди, Е. Сведенборга, Л. Шестова), містичного, як у випадку з М. Гоголем,
О. де Бальзаком, до прогностично аналітичного (В. Домонтович) і навіть побутово-вульгарного
(соцреалізм). Literature can interact with reality in many possible ways, and one of them is ‘derealization of reality’.
The term was introduced by Viktor Petrov (V. Domontovych) at the end of the 1940s; yet the first
reflections on this phenomenon in the discourse of the Ukrainian literature appeared in 1913 within
Mykola Yevshan’s articles on the specificity of Lesia Ukrainka’s creative work. Real Ukrainian life of
that time did not provide a proper material for the philosophical perspectives of her poetry; it didn’t
allow implementing the modernist aesthetics which were gradually developing in Europe and timidly
penetrating into Ukrainian culture. To a certain extent Lesia Ukrainka’s situation may be compared to
indispensability of the choice facing Gogol, who was compelled to write in Russian. This was, first of
all, the consequence of the low status of the Ukrainian language in Russian Empire.
In the study “Apotheosis of Groundlessness” (1905) Lev Shestov announced a new phase of
philosophical understanding of reality. He related a process of cognition with a subject of cognition, i.
e. with entire destiny of a human being. In his concepts of ‘derealization of reality’ and ‘groundlessness’
Viktor Petrov came close to Shestov’s existentialist ideas applied to the negativity and skepticism
as the life strategies. Petrov, in a similar way to that of Hryhorii Skovoroda, insisted on the absolute
autonomy of a person; he asserted one’s right to the critical perception of the world and even skeptical
attitude towards it.
The polysemy of the term ‘groundlessness’ allows using it in diverse contexts: from philosophical
(Skovoroda, Swedenborg, Shestov) and mystical (Gogol, Balzac) to analytical and prognostic (V.
Domontovych’s novel “Without Ground”), let alone the primitive meaning this term acquired in the
literature of socialist realism.